2012
DOI: 10.2460/ajvr.73.3.346
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of infusions of xylazine with ketamine or propofol to modulate recovery following sevoflurane anesthesia in horses

Abstract: Xylazine-ketamine or xylazine-propofol infusion significantly improved quality of recovery from sevoflurane anesthesia in horses. Xylazine-ketamine or xylazine-propofol infusions may be of benefit during recovery from sevoflurane anesthesia in horses for which a smooth recovery is particularly critical. However, oxygenation and ventilation should be monitored carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Pharmacological techniques aim to prolong recovery and allow the horse to eliminate the inhalant anaesthetic prior to regaining proprioception, and thus ensure a smoother and calmer recovery. Drugs such as alpha 2 agonists injections, propofol or ketamine infusions in combination with alpha 2 agonists infusion have been used; these studies have reported variable effects on recovery quality [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological techniques aim to prolong recovery and allow the horse to eliminate the inhalant anaesthetic prior to regaining proprioception, and thus ensure a smoother and calmer recovery. Drugs such as alpha 2 agonists injections, propofol or ketamine infusions in combination with alpha 2 agonists infusion have been used; these studies have reported variable effects on recovery quality [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This combination was shown to improve the quality of transition from lateral recumbency to standing but there was also a potential increase in respiratory depression (hypoventilation, hypoxaemia and apnoea). Wagner et al [ 12 ] failed to show any improvement of recovery quality when xylazine and ketamine CRIs, 20 μg/kg/min and 60 μg/kg/min respectively, were used for 30 min after stopping isoflurane.…”
Section: Introductionmentioning
confidence: 99%
“…Various anesthetics have been used in previous studies, including intraperitoneal injection of ketamine and xylazine (K/X), avertin (AV; also named tribromoethanol), chloral hydrate, barbiturates and thiobutabarbital, and inhaled volatile anesthetics, such as isoflurane and halothane (35). Among these, the K/X combination is one of the most widely used anesthetic approaches in animal experiments (6,7). In this combination, each component is suggested to compensate for the limitations of the other and to provide the most favorable anesthetic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Recovery was relatively smoother for dogs in Medetomidine-ketofol group compared to ACP-ketofol group. Propofol has been associated with smooth recovery from anesthesia and especially when combined with an apha-2-adrenergic [7,8]. The insignificant but notable difference in recovery between the study groups could be attributed to medetomidine and ketamine which have analgesic effects.…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits NMDA receptors by modulating channel gating [1]. Although associated with post-induction apnea [6], it produces smooth recovery, especially when combined with alpha-2-adrenoceptor agonists [7,8].…”
Section: Introductionmentioning
confidence: 99%